The star whale - Davies, Nicola 1958- (Otter-Barry Books, 2023)
Two superlative talents combine in a feast of verbal and visual imagery: forty brilliant poems celebrating the living world with love and laughter. Always inventive, with surprises and fresh perceptions on every page, these poems and pictures will captivate young readers. The range is astonishing, from the cosmic qualities of the Star Whale to the tiny but intense identities of a butterfly or a moth. The boundaries of time and space retreat in poems like 'Way back in the Old Cretaceous'. Raw realities are faced in the "tazzies" feast and fighting in 'A Night out in Tasmania'. There is magical vision in 'The Song of the Melting Tiger' and rude hilarity in 'Walking the Hippo'. From the Titanosaurus to the bat, the butterfly and the moth, trees and bees, toucans and turkeys, the tone move effortlessly from comic to lyrical or reflective
Keywords: Tiere -- Motiv; Kinderlyrik; Englisch; Animals / Juvenile poetry; Nature / Juvenile poetry; Children's poetry, English; Earth (Planet) / Pictorial works / Juvenile poetry; Nature / Poésie pour la jeunesse; Poésie enfantine anglaise; Terre / Ouvrages illustrés / Poésie pour la jeunesse; Nature poetry; Bilderbuch